2016
DOI: 10.1098/rstb.2015.0277
|View full text |Cite
|
Sign up to set email alerts
|

Plant diversity effects on grassland productivity are robust to both nutrient enrichment and drought

Abstract: Global change drivers are rapidly altering resource availability and biodiversity. While there is consensus that greater biodiversity increases the functioning of ecosystems, the extent to which biodiversity buffers ecosystem productivity in response to changes in resource availability remains unclear. We use data from 16 grassland experiments across North America and Europe that manipulated plant species richness and one of two essential resources—soil nutrients or water—to assess the direction and strength o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
205
5
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 192 publications
(235 citation statements)
references
References 62 publications
24
205
5
1
Order By: Relevance
“…The nutrient experiment, a factorial addition of N, P and K plus micronutrients, was replicated in three blocks per site. All plots were 5 Â 5 m and annually received 10 g N m 22 SO 4 ]. To avoid toxicity, 100 g m 22 yr 21 of a micronutrient mix of Fe (15%), S (14%), Mg (1.5%), Mn (2.5%), Cu (1%), Zn (1%), B (0.2%) and Mo (0.05%) was added only in the first treatment year.…”
Section: Methods (A) Datamentioning
confidence: 99%
See 1 more Smart Citation
“…The nutrient experiment, a factorial addition of N, P and K plus micronutrients, was replicated in three blocks per site. All plots were 5 Â 5 m and annually received 10 g N m 22 SO 4 ]. To avoid toxicity, 100 g m 22 yr 21 of a micronutrient mix of Fe (15%), S (14%), Mg (1.5%), Mn (2.5%), Cu (1%), Zn (1%), B (0.2%) and Mo (0.05%) was added only in the first treatment year.…”
Section: Methods (A) Datamentioning
confidence: 99%
“…Nutrient enrichment experiments show that eutrophication can reduce diversity by decreasing niche dimensionality and enhancing competitive exclusion via increased light limitation [4,5,8] or other resource limitation [21]. The effects of eutrophication may be dampened by higher plant diversity and functional composition [22]. Climate variability can contribute to the maintenance of diversity as species vary in their responses to climatic conditions [18,23,24].…”
Section: Introductionmentioning
confidence: 99%
“…A metastudy of this special issue integrates data from 16 grassland BEF experiments to address interactions between biodiversity and one of two essential resources (soil nutrients or water) on above-ground plant productivity [63]. The results indicate that the biodiversity effects on ecosystem functioning do not interact with the resources to affect productivity [63].…”
Section: Issue (2): Non-equilibrium Biodiversity and Ecosystem Functimentioning
confidence: 99%
“…A metastudy of this special issue integrates data from 16 grassland BEF experiments to address interactions between biodiversity and one of two essential resources (soil nutrients or water) on above-ground plant productivity [63]. The results indicate that the biodiversity effects on ecosystem functioning do not interact with the resources to affect productivity [63]. Another meta-study of this special issue, an experiment replicated at 32 grassland sites on four continents, addresses how eutrophication and climate affect the invasibility of plant communities by non-native species [64].…”
Section: Issue (2): Non-equilibrium Biodiversity and Ecosystem Functimentioning
confidence: 99%
“…Many studies have demonstrated that high species diversity enhances ecosystem functioning both in experimental and natural assemblages ( [1][2][3][4]; reviewed in [5] this issue). However, it has been argued elsewhere that it is not the total number of species per se, but the functional properties of the most locally abundant ones (hereafter common species) that drive ecosystem functioning (mass -ratio hypothesis [6]).…”
Section: Introductionmentioning
confidence: 99%